The effectiveness of maintenance infrastructure work in UiTM / Meor Mohd Fadzli Zahid - Zahid, Meor Mohd Fadzli (2005)
Infrastructures are the basic physical systems of a country or community’s population, which include roads, utilities, water, sewerage, etc. These systems are considered essential for enabling productivity in the economy. Infrastructures are one of the most important parts in a development process. Developing infrastructure often requires large initial investment, but the economies of scale tend to be significant. The objectives of the study are to study the type of maintenance works carried out on existing infrastructure in UiTM Shah Alam and to identify the items of works that constitutes the roads, drainage system, water supply, electrical and sewerage treatment plant maintenance work. The study also focuses on the management of maintenance works practiced by UiTM. The methodology adopted in the preparation of this dissertation in divided into two categories data collection and data analysis. Collections of data are from the primary data which is obtained from site visit and interviews of the associated parties at the Maintenance Department of UiTM.